Desain Multi Amfibi Ship Sebagai Sarana Evakuasi Tanggap Darurat Bencana Alam Banjir - Anauta Lungiding Angga Risdianto; Taufan Prasetyo; Lukman Hadiwijaya (Universitas Islam Raden Rahmat, Malang, 2024)
Indonesia is a tropical country, however, every year there is a reduction in forest area by 0.5% of the land area. This condition is the cause of flood disasters and high rainfall causes water to quickly fill the dam. From the existing problems it is necessary to make modifications as an effective means of evacuation. In this research we used the Reserch and Development (R&D) method by modifying between ships and land vehicles. The innovation carried out is the Multi Amphibian Boat. The results of the research are in the form of a conceptual design as an illustration for 1:1 manufacturing planning. The main size of the design is 3 m long; 1.2 m wide; 1.1 m high; and 0.5 m deep. The size selection is done to ensure that this facility can be used in small alleys so as to facilitate and speed up the evacuation of floods if they occur in urban areas or densely populated areas.